A Review of the Multidisciplinary Diagnosis of Interstitial Lung Diseases: A Retrospective Analysis in a Single UK Specialist Centre - Nazia Chaudhuri; Lisa Spencer; Colm leonard (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2015)
A multidisciplinary team approach to diagnosis and management of interstitial lung diseases (ILD) is  considered  gold  standard  and  an  integral  part  of  ILD  management  and  guidelines.The  accurate diagnosis and management of individuals with ILDs poses an interesting challenge in clinical practice. This  is  a  single  center  retrospective review  of  electronic  patient  letters  and  multidisciplinary  team (MDT) records spanning a five and half year time period. In this study we assessed the accuracy of prior ILD diagnosis, the methodology used to establish a correct diagnosis and how an MDT approach to diagnosis affected subsequent management. Our results demonstrate that a multidisciplinary approach to diagnosis within a single specialist ILD center can establish a diagnosis in the majority of cases when prior diagnosis is uncertain (76%). We  also  show  that  a  prior  diagnosis  of  idiopathic  pulmonary  fibrosis  is  deemed  inaccurate  in  over fifty percent of cases after MDT discussion. Other ILD diagnoses fair better with an inaccurate prior diagnosis  in  a  third  of  cases.  Over  time  we  demonstrate  an  increased  utilisation  of  combined  lung biopsy  and  radiological  imaging  to  establish  a  diagnosis.  However  when  diagnosis  was  deemed uncertain on radiological imaging alone, biopsy was seldom possible due to factors such as poor lung function or presence of comorbidities deeming biopsy as too high risk. Our  data  supports  an  MDT  approach  in  an  experienced  specialised  ILD  center.  We  have demonstrated that diagnosis is often changed after an MDT review and that this impacts on subsequent management.  We  have  shown  that  during  diagnostic  uncertainty  the  considered  gold  standard  of proceeding to a lung biopsy is not always feasible due to disease severity and comorbidities. In these circumstances an MDT approach to diagnosis of ILDs combines clinical data with serial lung function and disease behavior, with or without responses to previous treatment trials to establish an accurate expert diagnosis.